1986
DOI: 10.1126/science.3775363
|View full text |Cite
|
Sign up to set email alerts
|

The Brain Nucleus Locus Coeruleus: Restricted Afferent Control of a Broad Efferent Network

Abstract: Dense, focal injections of wheat germ agglutinin conjugated-horseradish peroxidase in the locus coeruleus of rats labeled afferent neurons in unexpectedly few brain regions. Major inputs emanate from only two nuclei--the paragigantocellularis and the prepositus hypoglossi, both in the rostral medulla. The dorsal cap of the paraventricular hypothalamic nucleus and the spinal intermediate gray are possible minor afferents to locus coeruleus. Other areas reported to project to locus coeruleus (for example, amygda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
277
1
2

Year Published

1987
1987
2009
2009

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 725 publications
(295 citation statements)
references
References 58 publications
15
277
1
2
Order By: Relevance
“…One possible mechanism to explain the effect of metyrapone on delta sleep is that the increase in PVN CRF release affects other brain areas involved in sleep or arousal. This possibility is supported by studies that have shown that some PVN CRF neurons project to the locus ceruleus (Aston- Jones et al, 1986;Valentino et al, 1992). For example, Valentino et al (1992) showed that retrograde labeling of CRF terminals in the locus ceruleus originated in the PVN.…”
Section: Discussionmentioning
confidence: 80%
“…One possible mechanism to explain the effect of metyrapone on delta sleep is that the increase in PVN CRF release affects other brain areas involved in sleep or arousal. This possibility is supported by studies that have shown that some PVN CRF neurons project to the locus ceruleus (Aston- Jones et al, 1986;Valentino et al, 1992). For example, Valentino et al (1992) showed that retrograde labeling of CRF terminals in the locus ceruleus originated in the PVN.…”
Section: Discussionmentioning
confidence: 80%
“…Thus, the reduction of inhibitory inputs from the raphe nuclei to the LC after lesion of the SNc causes an increase of activity of LC noradrenergic neurons. The LC also receives excitatory glutamatergic afferents from the paragigantocellularis nucleus [20] .…”
Section: Resultsmentioning
confidence: 99%
“…(Foote et al, 1983;Aston-Jones et al, 1986. It is worth noting that A6 neurons may also play a role in respiratory control because they display a respiratory-modulated firing, are sensitive to hypoxia, and may contribute to long-term adaptation to hypoxia (Guyenet et al, 1993;Dobbins and Feldman, 1994;Oyamada et al, 1998;Ballantyne and Scheid, 2000;Roux et al, 2000aRoux et al, , 2000b.…”
Section: Possible Contribution Of A6 Neurons To Rrg Prenatal Maturationmentioning
confidence: 99%